Pedagogic and Professional Competence of Islamic Religious Education Teachers at MTsN 3 East Aceh - Marlina Siregar; Nurbayani Nurbayani; Sukamto Sukamto; Najamuddin Petta Solong; Bambang Irawan (Faculty of Tarbiyah and Teaching Sciences, Universitas Islam Negeri Raden Fatah Palembang, 2023)
Good pedagogical and professional competence of teachers will have implications for the graduates produced. The learning process of Islamic education that is in accordance with the standards and also taught by professional teachers will have implications for the quality of Islamic religious education learning itself. Currently, research on the learning process of Islamic religion that is in accordance with the standards, namely taught by professional teachers, has not been widely studied. Therefore, in this study, researchers were interested in discussing these issues precisely in the MTsN 3 East Aceh. The research method used was descriptive qualitative research. In collecting data, researchers conducted observations and interviews with five participants. The collected data were analyzed using interactive data analysis techniques. The results showed that Islamic education teachers at MTsN 3 East Aceh have met the criteria for pedagogical competence and are included in the category of professional teachers.